Gentrification through the sale of rental housing? Evidence from Amsterdam - Jan Rouwendal; Adriaan Keus; Jasper Dekkers (Tinbergen Institute, 2018)
This paper analyzes the impact of the sale of rental housing in Amsterdam on the local housing market. This increases the supply of owner-occupied housing, but can also contribute to gentrification associated with the inflow of different household groups. Earlier literature focused on the former effect and reported a negative price effect. We take a fresh look at the issue by considering the sale of private as well as social rental housing, allow for differing time trends within the municipality, controlling for area fixed effects, distinguishing between short and long-term impacts and addressing endogeneity of the sale of rental housing. The main finding is a robust gentrifying effect of the sale of private rental housing in the core area of Amsterdam.
Keywords: R21; R23; R31; 330; gentrification; social housing; Dutch housing market